Modernization of the Russian Education Under the Geopolitical Realities of Modernity: The Problem of Formation of the Russian Identity - Lukash, Sergey Nikolaevich; Andrienko, Nadezhda K.; Tersakova, Angela A.; Pluzhnikova, Elena A. (Journal of History Culture and Art Research, 2019)
The obvious contradiction between a modern geopolitical course of the country to multi-polarity, to the Eurasian vector of development and the strategy of modernization of Russian education according the Western (European) model derivative of the idea of uni-polarity, embedding the Russian education in a valuable semantic paradigm of the Western civilization is being implemented till present. The contradiction related to the strategic geopolitical vector of development of modern Russia and the strategy of its state institutes, education, in particular, leads to the fact that in the Russian society the complex unresolved humanitarian problems will turn into a serious crisis in future. One of such challenges in Russia aggravated due to the global opposition between Russia and the USA is the problem of national unity of Russian society, the formation of Russian national identity. Variants of the pedagogical solution of the given problem actualizing the idea of multi-polarity and the paradigm of the Russian Eurasian civilization corresponding to it, in particular, the Cossacks phenomenon are considered in the article. In this aspect, the Cossack culture appears as a spiritual and ideological phenomenon of Russian civilization, as the national value, actualizing the idea of the personifying the idea of Russianness in the Eurasian vector of development of Russia, creating the traditional basis for Russian identity formation among the younger generations at present and in future.